P05.34 Multidisciplinary treatment in patients with leptomeningeal metastasis from gastric cancer in the era of individualized treatment: A single-institution, retrospective study. (19th September 2018) - Mitsuya, K; Yoko, N; Shoichi, D; Hayashi, N; Yasui, H; Harada, H
Abstract: Background: Leptomeningeal metastasis (LM) is a devastating complication of systemic cancers. New effective therapies for primary cancers have underscored the clinical significance of LM. We reviewed the outcomes of patients with LM from gastric cancer (LM-G) treated in our institute. Methods: Data on patients with LM-G diagnosed by cytological examination or MR images were retrospectively analyzed. Fourteen LM-G patients were treated between January 2005 and December 2016. Patients underwent intrathecal chemotherapy with methotrexate (it-MTX) and whole brain radiotherapy (WBRT) followed by systemic chemo-therapy, if they had KPS more than 40% and life expectancy longer than three months after control of their LM-G. Decision making of treatments was based on clinical manifestations, and was discussed at our cancer board on the individual situation. CSF shunt was indicated for patients with hydrocephalus or uncontrollable intracranial hypertension. Results: Of the 14 patients, 12 (86%) were male, and the median age was 63 years (range, 30–73). The median time from the diagnosis of gastric cancer to the onset of LM-G was 14 months. Symptoms were headache in 12 patients e, and ataxia in 2 patients. The median survival time from the onset of LM-G was 3.5 months. The longest survivor lived for 18 months (n=2). Median survival time was 7 months in patients who underwent all of it-MTX, RT and systemic chemotherapy (n=6) compared to 2 months in patients with it-MTX and RT alone (n=8) (p = 0.003). Most favorable prognostic group was chemotherapy-naïve patients LM-G who completed triple modality treatment, their mOS-LM was 17 months (n=3). Two patients achieved complete response after it-MTX, WBRT and systemic chemotherapy with a regimen of "cisplatin and S-1". CSF shunt surgery yielded patient palliation effects (n=5). Conclusion: Combination of triple modalities, it-MTX, WBRT and systemic therapy, is a safe and effective strategy in patients with LM-G. Because of palliative nature of the treatments for patients with LM-G, we need to clarify indications of interventional treatments on the basis of multi-institutional cohort.